Fabrication of Ag3PO4 /g-C3N4 composite: enhanced charge separation and outstanding photoactivity under very low intensity visible light irradiation - Mohamad Mukhair, Hayati; Abdullah, Abdul Halim; Mohd Hir, Zul Adlan; Osman, Nur Syazwani; Mohamed, Mohamad Azuwa; Mastuli, Mohd Sufri (2018)
A visible light driven Ag3PO4/g-C3N4 composite photocatalyst was synthesized by a simple coprecipitaion method by changing the loadings of g-C3N4 for degradation of methyl orange (MO) dye under very low visible light intensity. The results revealed that the introduction of g-C3N4 onto Ag3PO4 surface greatly improved its stability and photocatalitic activity. It was found that Ag3PO4/g-C3N4 with mass ratio Ag3PO4:g-C3N4 of 1:0.03 exhibited 98% of degradation under 20 minutes of irradiation time. The study proved that h+ played the chief role in the degradation process and a possible heterojunction mechanism was proposed.